Threshing naked oat in moist conditions - Kirkkari, Anna-Maija; Peltonen-Sainio, Pirjo (MTT, 2004)
For naked oat the aim is to maximise the yield free from lemma and palea and minimise threshing loss and grain damage. The fatty grains are, however, soft, and harvest at a high moisture content (in Finland usually harvested at 20% moisture content or higher) further increases the softness of the grain. Mechanical injuries also reduce germination through making the grains vulnerable to fungal infections that reduce storability. Two naked oat cultivars (Lisbeth and Bullion) and one conventional oat (Salo) were harvested at different grain moisture content using three combine harvester settings: the first setting was that recommended for conventional oat, the second used a reduced cylinder speed and the third used a narrow concave clearance. It was investigated whether grain moisture at threshing and combine harvester settings affected germination and hull content. The greater the grain moisture content of naked oat at harvest, the more damage was caused by threshing. Lower cylinder speeds tended to result in better germination than higher speeds, even under moist conditions. Narrowing the concave clearance did not affect germination. Threshing settings had only limited effects on hull content and degree of hull retention, and the postulated protective nature of hulls was confirmed only for cultivar Lisbeth. Threshing a naked oat crop at a low as possible grain moisture content can reduce harvesting damage. However, if this is not possible, better germination can be ensured by reducing the cylinder speed. Small grains tended to retain hulls more tightly during threshing. This may indicate that the most advanced grains were more completely filled and mature and therefore, also better able to dehull.
Keywords: Ka; kaura; paljasjyväinen kaura; kuoreton kaura; itävyys; jyvä; jyväkosteus; jyväydin; puinti; leikkuupuimuri; kuori; varastointi; naked oat; germination; grain moisture; harvester settings; hull